An ethnobotanical study of medicinal plants in Acipayam (Denizli-Turkey) - DOĞAN, AHMET; EMRE, GİZEM (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2017)
A comprehensive ethnobotanical study was conducted in Acipayam, situated in the western part of Turkey. This paper includes details of plants used in folk medicine and ethnopharmacological information obtained during this study. The aim of the authors was to collect and identify plants used by local people for therapeutic purposes and to present information about traditional herbal medicine. Plant specimens collected during field-work form the subject of this investigation. Information was obtained by means of open and semi-structured interviews with local people. In addition, cultural importance index (CI) and use report (UR) values were calculated. Ninety-one taxa of plants used in folk medicine and belonging to 38 families were identified in this study. Of these, 82 species were wild, and 9 species were cultivated. The most common families were Lamiaceae (18.7%), Asteraceae (14.3%) and Rosaceae (6.6%). Consequently, 191 medicinal uses (remedies) of 91 taxa were recorded. According to the use reports (UR), the most important medicinal plants were Cydonia oblonga (99 UR), Juniperus oxycedrus subsp. oxycedrus (99 UR), Pinus brutia (98 UR), Hypericum perforatum (90 UR), Viscum album subsp. austriacum (82 UR) and Salvia tomentosa (80 UR). Infusion (38.2%) was the most common preparation method used within the research area. The ethnomedicinal capabilities of eight species (Amelanchier parviflora var. dentata, Echinops viscosus subsp. bithynicus, Onopordum sibthorpianum, Origanum hypericifolium, Quercus trojana, Salvia adenophylla, Sideritis montana. subsp. remota and Tamarix smyrnensis) have been recorded for the first time in Turkey.
Keywords: Ethnobotany; Folk medicinal plants; Acipayam; Denizli; Turkey; NAVARRA IBERIAN PENINSULA; TRADITIONAL MEDICINE; FOLK MEDICINE; PHARMACEUTICAL ETHNOBOTANY; WILD PLANTS; PROVINCE TURKEY; WEST ANATOLIA; ANTIMICROBIAL ACTIVITIES; NORTHWEST TURKEY; ANKARA PROVINCE